1970
DOI: 10.3329/bja.v7i2.6096
|View full text |Cite
|
Sign up to set email alerts
|

Stature Estimation Using Head Measurements in Bangladeshi Garo Adult Females

Abstract: Context: Stature is the height of the person in the upright posture. It is an important measure of physical identity. Interrelationships among different body measurements may be used to estimate one from another in case of missing body parts. As any part of the human skeleton can be found as the evidences, there arise a need to investigate whether there is any possible significant correlation between stature and any parts in human body. Garos, our study subject living in Bangladesh are usually recognized as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 4 publications
0
15
2
Order By: Relevance
“…2 Akhter Z et.al examined head circumference and length of 100 Garo female subjects were included from Dhaka city and Mymensingh district, Bangladesh and advised head circumference showed significant positive correlation with stature but head length did not reach statistically significant level with stature. 8 Bhavna et.al have been studied on 503 male Shiah Muslim of Delhi, India and reported a body dimension which correlates highly with stature. 3 Ebite LE, et.al in their study on 109 healthy adults (45 male and 66 female) at Urome, Edo state, Nigeria and derived a formula based on Ulna length.…”
Section: Discussionmentioning
confidence: 99%
“…2 Akhter Z et.al examined head circumference and length of 100 Garo female subjects were included from Dhaka city and Mymensingh district, Bangladesh and advised head circumference showed significant positive correlation with stature but head length did not reach statistically significant level with stature. 8 Bhavna et.al have been studied on 503 male Shiah Muslim of Delhi, India and reported a body dimension which correlates highly with stature. 3 Ebite LE, et.al in their study on 109 healthy adults (45 male and 66 female) at Urome, Edo state, Nigeria and derived a formula based on Ulna length.…”
Section: Discussionmentioning
confidence: 99%
“…Some matched samples were published under ethnonyms, these were also combined. Stature data from reports that included only one gender were excluded, except in the case of the Garo, where two separate samples (one of males and one of females) were combined (Akhter, Banu, Alam, & Rahman, ; Jaswal, ). Any sample with a stated number of less than 20 individuals of either gender was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Correlation coefficients between the personal stature and OFC among Sri Lankans were found to be statistically significant and positive (0.62 in male and 0.86 in female) indicating a strong relationship between the two parameters. Previous studies have shown correlation coefficients of 0.78 in North Indian males (Krishan), 0.44 in Nepalese male and 0.32 Nepalese females 0.32 (Mansur et al, 2014), 0.4 in Bangladesh male and 0.3 in Bangladesh female (Akhter et al, 2009). 0.34 in Canadian male (Nguyen et al).…”
Section: Discussionmentioning
confidence: 95%